PENGARUH KOMPETENSI, PENGEMBANGAN SUMBER DAYA MANUSIA, DAN MOTIVASI TERHADAP KINERJA PEGAWAI RSUD EMBUNG FATIMAH KOTA BATAM - Jurnal Ilmiah Manajemen UPB (Universitas Putera Batam, 2017)
This research intend to know and analysis the influences of the Competence, Human Resources Development, and Motivation factors towards employee performances in the RSUD Embung Fatimah Batam. The result of collecting data with primary data source from 120 respondents of the employee in the RSUD of Embung Fatimah Batam. The kinds of research are explanatory case study and analysis method using multiple regression analysis, with using method to exam with validities person rank and reliabilities cronbach alpa exam toward research instrument. The result of the research and evaluation are shown that Competence, Human Resources Development, and Motivation factors have positive influences and significant towards employee performance as good as stimulant or partial.